Google Site as a Learning Media in the 21st Century on the Protists Consept - Dieny Aulia; Kaspul Kaspul; Maulana Khalid Riefani (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The development research was carried out using the 4D development model adapted from Thiagarajan. This research and development aims to create and develop learning media that can support the learning process. The website-based learning media for the Protista concept for tenth grade Biology High School is carried out because of the importance of technology-based media innovation in 21st-century learning. The learning media developed is a website using google site equipped with a combination of text, images, animation, audio, video, and a simply designed navigation bar. The research and development of this website-based learning media uses a 4D development model (Define, Design, Develop, and Disseminate), but this research is focused on the responses of students in using the google sites learning media. The results of student responses to the learning media website